Kemalasan dalam Perspektif Kitab Amsal - Ragil Kristiawan (Jurnal Ilmiah Tafsir Alkitab, 2024)
Abstract Proverbs discusses issues that are relevant to everyone wherever they are. This book discusses horizontal issues regarding human relationships with each other. One issue that is quite important is laziness which has become a comprehensive problem in human life today. No previous research has conducted a biblical study regarding laziness from the perspective of the book of Proverbs. This research tries to answer the problem of how Proverbs views laziness. Through literature study using thematic interpretation of Proverbs, an assessment of lazy attitudes based on this book was produced: this attitude will not bring any benefits at all. For those who expect satisfactory results from lazy people, it will definitely result in disappointment. Laziness will give birth to forced labor, you will not succeed in everything you do, you will become the brother of the destroyer, you will starve, you will never reap, and you will not get anything in your life. The lazy person's life will ultimately be killed by his desires. The Book of Proverbs gives advice to lazy people so that they continue to learn from ants in terms of discipline. Even though ants are weak animals, they are famous for their craft. In the end, discipline is an effective medicine for all lazy attitudes that arise in the lives of believers in all places and times. Keywords: Lazy, Point of View, Proverbs Abstrak Kitab Amsal membicarakan topik-topik persoalan yang relevan dengan semua orang dimanapun mereka berada. Kitab ini membahas isu-isu horisontal berkenaan dengan hubungan manusia dengan sesamanya. Salah satu isu yang cukup penting adalah mengenai kemalasan yang telah menjadi masalah menyeluruh dalam kehidupan manusia di jaman sekarang. Penelitian-penelitian terhahulu belum ada yang melakukan kajian biblika mengenai kemalasan dalam sudut pandang kitab Amsal. Penelitian ini mencoba menjawab permasalahan tentang bagaimana cara pandang Amsal mengenai kemalasan. Melalui studi kepustakaan dengan menggunakan pendekatan tematis atas Amsal, maka dihasilkan penilaian akan sikap malas berdasarkan kitab ini: sikap ini sama sekali tidak akan membawa keuntungan. Bagi mereka yang mengharapkan hasil memuaskan dari orang yang malas pasti akan membuahkan kekecewaan. Kemalasan akan melahirkan kerja paksa, tidak akan berhasil dalam segala hal yang dilakukan, menjadi saudara si perusak, akan mengakibatkan kelaparan, tidak pernah menuai, serta tidak akan mendapatkan apapun dalam kehidupannya. Kehidupan si pemalas pada akhirnya akan dibunuh oleh keinginannya. Kitab Amsal memberikan saran kepada pemalas untuk mereka terus belajar kepada semut dalam hal kedisiplinan. Walaupun semut binatang yang lemah, tetapi mereka terkenal akan kerajinannya. Pada akhirnya, kedisiplinan merupakan obat yang ampuh bagi segala sikap malas yang timbul dalam kehidupan orang percaya di segala tempat dan jaman. Kata kunci: Malas, Sudut Pandang, Kitab Amsal